Glipang Rodhat: Symbolic Mediation in Divorce Resolution - Isriyah, Mudafiatun (International Asia Of Law and Money Laundering (IAML), 2024)
This research investigates the role of Glipang Rodhat, a symbolic mediation tradition, in divorce settlement. Glipang Rodhat, a traditional art form in Lumajang, East Java, has emerged as an alternative mediation method for addressing marital conflicts. By employing a multi-method approach, this study aims to comprehensively examine the effectiveness of Glipang Rodhat in facilitating fair and sustainable resolution processes. The research focuses on analyzing the symbolic representations embedded in dance movements within Glipang Rodhat performances. Through the collection of data from diverse cultural contexts, the study seeks to provide a nuanced understanding of the global dynamics influencing the mediation process. Ultimately, this research aims to identify the significance of symbolic mediation in fostering a sense of unity and interconnectedness in divorce resolution. By shedding light on the intricate relationship between cultural symbolism and conflict resolution strategies, the study contributes to the development of more holistic approaches to mediation practices.